High ionic conductivity Li0.33La0.557TiO3 nanofiber/polymer composite solid electrolyte for flexible transparent InZnO synaptic transistors. (16th July 2021) - Fu, Wenhui; Li, Jun; Li, Linkang; Jiang, Dongliang; Zhu, Wenqing; Zhang, Jianhua
Abstract: With the rapid development of wearable artificial intelligence devices, there is an increasing demand for flexible oxide neuromorphic transistors with the solid electrolytes. To achieve high-performance flexible synaptic transistors, the solid electrolytes should exhibit good mechanical bending characteristics and high ion conductivity. However, the polymer-based electrolytes with good mechanical bending characteristics show poor ion conductivity (10 −6 –10 −7 S cm −1 ), which limits the performance of flexible synaptic transistors. Thus, it is urgent to improve the ion conductivity of the polymer-based electrolytes. In the work, a new strategy of electrospun Li0.33 La0.557 TiO3 nanofibers-enhanced ion transport pathway is proposed to simultaneously improve the mechanical bending and ion conductivity of polyethylene oxide/polyvinylpyrrolidone-based solid electrolytes. The flexible InZnO synaptic transistors with Li0.33 La0.557 TiO3 nanofibers-based solid electrolytes successfully simulated excitatory post-synaptic current, paired-pulse-facilitation, dynamic time filter, nonlinear summation, two-terminal input dynamic integration and logic function. This work is a useful attempt to develop high-performance synaptic transistors.